101 great science experiments : a step by step guide - Ardley, Neil. (London : Dorling Kindersley, 1994)
Describes 101 science experiments or activities that can be done with household items and easily found ingredients.
Include index.
Keywords: Scientific recreations -- Juvenile literature; Science -- Experiments -- Juvenile literature